The inter- and multi- generational epigenetic alterations induced by maternal cadmium exposure - Lawless, Lauren; Xie, Linglin; Zhang, Ke (Frontiers in Cell and Developmental Biology, 2023)
Exposure to cadmium during pregnancy, from environmental or lifestyle factors, has been shown to have detrimental fetal and placental developmental effects, along with negatively impacting maternal health during gestation. Additionally, prenatal cadmium exposure places the offspring at risk for developing diseases in infancy, adolescence, and adulthood. Although given much attention, the underlying mechanisms of cadmium-induced teratogenicity and disease development remain largely unknown. Epigenetic changes in DNA, RNA and protein modifications have been observed during cadmium exposure, which implies a scientific premise as a conceivable mode of cadmium toxicity for developmental origins of health and disease (DOHaD). This review aims to examine the literature and provide a comprehensive overview of epigenetic alterations induced by prenatal cadmium exposure, within the developing fetus and placenta, and the continued effects observed in childhood and across generations.